A randomized prospective long-term (>1 year) clinical trial comparing the efficacy and safety of radiofrequency ablation to 980 nm laser ablation of the great saphenous vein. (July 2017) - Sydnor, Malcolm; Mavropoulos, John; Slobodnik, Natalia; Wolfe, Luke; Strife, Brian; Komorowski, Daniel
Purpose: To compare the short- and long-term (>1 year) efficacy and safety of radiofrequency ablation (ClosureFAST™) versus endovenous laser ablation (980 nm diode laser) for the treatment of superficial venous insufficiency of the great saphenous vein. Materials and methods: Two hundred patients with superficial venous insufficiency of the great saphenous vein were randomized to receive either radiofrequency ablation or endovenous laser ablation (and simultaneous adjunctive therapies for surface varicosities when appropriate). Post-treatment sonographic and clinical assessment was conducted at one week, six weeks, and six months for closure, complications, and patient satisfaction. Clinical assessment of each patient was conducted at one year and then at yearly intervals for patient satisfaction. Results: Post-procedure pain ( p < 0.0001) and objective post-procedure bruising ( p = 0.0114) were significantly lower in the radiofrequency ablation group. Improvements in venous clinical severity score were noted through six months in both groups (endovenous laser ablation 6.6 to 1; radiofrequency ablation 6.2 to 1) with no significant difference in venous clinical severity score ( p = 0.4066) or measured adverse effects; 89 endovenous laser ablation and 87 radiofrequency patients were interviewed at least 12 months out with a mean long-term follow-up of 44 and 42 months ( p = 0.1096), respectively. There were four treatment failures in each group, and every case was correctable with further treatment. Overall, there were no significant differences with regard to patient satisfaction between radiofrequency ablation and endovenous laser ablation ( p = 0.3009). There were no cases of deep venous thrombosis in either group at any time during this study. Conclusions: Radiofrequency ablation and endovenous laser ablation are highly effective and safe from both anatomic and clinical standpoints over a multi-year period and neither modality achieved superiority over the other.